Anglo-Gascon Aquitaine problems and perspectives - Anglo-Gascon Aquitaine: Problems and Perspectives; Pépin, Guilhem 1976-; Arts & Humanities Research Council; Conference Anglo-Gascon Aquitaine, problems and perspectives (The Boydell Press, 2017)
"The political union between England and Gascony or Aquitaine lasted from the early thirteenth century until 1453, and the long series of Gascon Rolls in the National Archives record some of the business of Aquitaine during the union. These are currently being calendared, and this volume reflects some of the research which resulted. The administration and record production of the Anglo-Gascon officials, and their relationship with the English , including its social and political implications is directly connected to the calendars. New light is shed on the origins of the war of Saint-Sardos in 1323, and on the recruitment of English criminals in Edward II's army when war actually broke out. From 1361 onwards, Edward prince of Wales (the Black Prince) was also prince of Aquitaine, and two essays are concerned with the period of his rule, which ended disastrously in 1369. The French campaign to retake Gascony dates from this year, and allegiances both in Gascony and in the neighbouring principalities are studied using the material in the rolls. Matters were further complicated by the great papal schism, when French and English backed different candidates for the papacy, and the political division became a religious one as well."